A novel concept of pseudo ternary diffusion couple for the estimation of diffusion coefficients in multicomponent systems. (1st April 2018) - Esakkiraja, Neelamegan; Paul, Aloke
Abstract: A pseudo ternary diffusion couple technique in a multicomponent system by simplifying the mathematical complications of Onsager formalism is proposed for the estimation of composition dependent values of the interdiffusion coefficients. This is otherwise impossible following the conventional method in a system with more than three components. Other alternative methods estimate the average diffusion coefficients over a composition range of random choice and lack physical significance. This method can be followed in a multicomponent system with any number of components on the condition that only three components develop diffusion profiles keeping others as constant. Graphical abstract: Image 2